Functional group tolerant hydrogen borrowing C-alkylation - Bailey, EP; Donohoe, TJ; Smith, MD (Nature Research, 2024)
Hydrogen borrowing is an attractive and sustainable strategy for carbon–carbon bond formation that enables alcohols to be used as alkylating reagents in place of alkyl halides. However, despite intensive efforts, limited functional group tolerance is observed in this methodology, which we hypothesize is due to the high temperatures and harsh basic conditions often employed. Here we demonstrate that room temperature and functional group tolerant hydrogen borrowing can be achieved with a simple iridium catalyst in the presence of substoichiometric base without an excess of reagents. Achieving high yields necessitates the application of anaerobic conditions to counteract the oxygen sensitivity of the catalytic iridium hydride intermediate, which otherwise leads to catalyst degradation. Substrates containing heteroatoms capable of complexing the catalyst exhibit limited room temperature reactivity, but the application of moderately higher temperatures enables extension to a broad range of medicinally relevant nitrogen rich heterocycles. These newly developed conditions allow alcohols possessing functional groups that were previously incompatible with hydrogen borrowing reactions to be employed.